2001
DOI: 10.1093/gerona/56.8.m505
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Depression and Mortality in Elderly Persons: A Case for Multiple, Independent Pathways

Abstract: The estimated odds of dying if depressed moved toward unity as other risk factors for mortality were controlled. Unlike other known risk factors for mortality in the elderly population, depression appears to be associated with mortality through a number of independent mechanisms, perhaps through complex feedback loops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
156
4
10

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(178 citation statements)
references
References 19 publications
8
156
4
10
Order By: Relevance
“…Several other studies found that depressive disorder is associated with body mass index [39,40] and obesity [41], especially among subjects with severe obesity. Depressive disorders also have been found to be associated with lower physical activity [17•], and with a larger number of fatal accidents [42].…”
Section: Other Hazardous Health Behaviorsmentioning
confidence: 96%
“…Several other studies found that depressive disorder is associated with body mass index [39,40] and obesity [41], especially among subjects with severe obesity. Depressive disorders also have been found to be associated with lower physical activity [17•], and with a larger number of fatal accidents [42].…”
Section: Other Hazardous Health Behaviorsmentioning
confidence: 96%
“…Furthermore, depression may act on mortality through multiple relatively independent pathways, which pathways may lead to double feedback loops. For example: depression is known to increase the likelihood of functional impairment, and functional impairment in turn, is a risk factor for depression (Penninx et al, 2000;Blazer et al, 2001).…”
Section: Explanationsmentioning
confidence: 99%
“…The risk for mortality in elderly patients diagnosed with depression doubles when the patients are followed over 3 years. 3 Although much of this research has focused on major depression, clinically significant depressive symptoms, which are more prevalent than major depression as they affect 3e26% of community-dwelling old adults, have received little attention in the literature. 2 Although depressive symptoms do not meet the diagnostic criteria for major depression and thus are not considered to be as severe, the consequences of significant depressive symptoms, including functional impairment, medical morbidity, and increased health care costs, are quite similar to those of major depression.…”
Section: Introductionmentioning
confidence: 99%